Contribuições dos jogos de papéis para o desenvolvimento das funções psicológicas superiores - Colussi, Lisiane Gruhn (2016)
In the perspective of Cultural-Historical Theory, based on Vygotski, Leontiev and Elkonin, child development is conceived as a historical and dialectic phenomenon, determined by the objective conditions of social organization. In this manner, it comprehends several psychic stages characterized by distinct forms of relating with the world and by different guide-activities, responsible for this process, being that role playing games are the fundamental guide-activity from ages three to six. In the present study, the objective was to verify the contribution of role playing games towards the development of superior psychological functions in children from ages five to six. To accomplish this, the specific objectives were: study the “state of knowledge”, about the periodization of psychic development in Children‟s Education, in the period between 2004-2014; analyze the contributions of the Cultural-Historical Psychology in order to comprehend psychic development of the young child; describe role playing games experienced by children ages five to six; investigate the dynamic of interactions and of negotiations relative to the roles played by the children during role playing games; identify how functional psychological processes manifest during role playing games. To reach these specific objectives a qualitative field survey was developed in a public school, involving 12 students in Children´s Education, in this age range, and the teacher. Data collection was organized into two phases. In Phase I, a pilot survey took place that consisted in observing “Toy Day” (name given in the classroom routine) during six hours with the intention of responding some questions to better guide the planning of Phase II. This phase involved filming role playing games, over the course of 15 days, involving six sessions, with an average duration of 45 minutes each, summing a total of five hours of footage, that were then transcribed for analysis. The research about the State of Knowledge, together with the data collected in Phase I revealed the lack of knowledge about role playing games as a factor in infantile psychological development. The analysis of role playing games collected during Phase II demonstrated that the protagonized children‟s experiences improve the superior functional processes of the children, which enables them to be more active since it favors interactions that make the exchange of experiences between children and adults possible. This way, role playing games are a way of cultural appropriation of the social relations produced in the context into which the child inserts himself in, making it possible for the child to recognize his or her capacity and potential, demonstrate his or her feelings and moral and ethic judgments, and reveal his or her conscience in seek of humanization. Thus, it is important for the teacher to recognize and favor the educative potential of role playing games.